Extension Programs in Northeastern Florida Help Growers Produce Quality Strawberries by Improving Water and Nutrient Management - Robert Hochmuth; David Dinkins; Michael Sweat; Eric Simonne (EDIS)
The Florida strawberry industry is primarily located in the Plant City area with approximately 6,000 acres. There is scattered acreage in other parts of the state including Bradford County and the surrounding area of northeastern Florida. The Bradford County area was once the main strawberry producing area in the state with 1500 acres of strawberries grown during the period of 1915 to 1920. This rich heritage is still important to Bradford County's economy today. Strawberry acreage in northeastern Florida (Gainesville and north) was estimated at 40 acres in 2003. This document is HS-956, one of a series of Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2003.